Paradox of Success-Mediated Conflicts: Analysing Attitudes of Local Communities Towards Successfully Reintroduced Tigers in India - Malviya, Manjari; Kalyanasundaram, Sankar; Krishnamurthy, Ramesh (Frontiers in Conservation Science, 2022)
Conservation programs like reintroductions are pivotal for the survival and proliferation of endangered species like tigers. However, restoring carnivore population may create unforeseen problems for the communities by fueling human–wildlife conflict. Long-term persistence of tigers can only be ensured when the support of these local communities is garnered for conservation efforts, especially in release sites from where they were initially eliminated due to anthropogenic causes. And the first step to gaining support for tigers and their reintroduction programs is to understand how local communities perceive these large carnivores. This study thus assessed the attitudes of local communities towards the reintroduced tigers of India, in Panna and Sariska Tiger Reserves, and examined the socio-economic factors that potentially shape their attitudes. Questionnaire surveys were conducted in 330 households across 25 villages in Panna, and 361 households across 32 villages in Sariska. Decision tree and multinomial logistic regression analyses were employed to identify the explanatory variables associated with attitudes. In Panna, more respondents (52.12%) expressed negative opinions about tiger, as compared to positive (24.55%). Whereas in Sariska, more respondents had positive opinions (47.92%) than negative (34.90%). In both the sites, the most frequent reason given by the respondents for their negative attitude towards tigers was ‘fear’. Regression modeling suggests that gender and education are key factors associated with the attitude of local communities towards reintroduced tigers. Other factors, specific to the reserves, were age of the respondent, age of lost livestock, compensation received, and value of fodder obtained from reserve. Community engagement must be integrated into conservation projects with a focus on educating women and the elderly about carnivores, protecting the traditional rights of local communities, and compensating their losses.